(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Communicative language teaching (CLT), or the communicative approach (CA) , is an approach to language teaching that emphasizes interaction[as both the means and the ultimate goal of study. Learners in environments using communication to learn and practice the target language by interactions with one another and the instructor, the study of "authentic texts" (those written in the target language for purposes other than language learning), and the use of the language both in class and outside of class.